Long-Term Effects of the Rain Exposure Shortly after the Atomic Bombings in Hiroshima and Nagasaki - Sakata, Ritsu; Grant, Eric J.; Furukawa, Kyoji; Misumi, Munechika; Cullings, Harry; Ozasa, Kotaro; Shore, Roy E. (Radiation research, 2014)
The “black rain” that fell after the atomic bombings of Hiroshima and Nagasaki has been generally believed to contain radioactive materials. During 1949–1961 the Atomic Bomb Casualty Commission conducted surveys that included a query about exposure to the rain that fell a short time after the bombings. This article presents the first report of those data in relation to possible adverse health outcomes. This study looked at Life Span Study subjects who were in either city at the time of bombing and had an estimated direct radiation dose from the bombs (n = 86,609). The mortality data from 1950–2005 and cancer incidence data from 1958–2005 were used. Excess relative risks (ERRs) of subjects who were exposed to rain compared to those who reported no rain exposure were calculated using a Poisson regression model. In Hiroshima 11,661 subjects (20%) reported that they were exposed to rain, while in Nagasaki only 733 subjects (2.6%) reported rain exposure. To avoid outcome dependent biases (i.e., recall of exposure after a health outcome has already occurred), the primary analyses were based on events that occurred during 1962–2005. No significant risks due to rain exposure were observed for death due to all causes, all solid cancer or leukemia in Hiroshima. In Nagasaki there was no significantly elevated rain exposure-associated risks for 1962–2005, however, for 1950–2005 there was a weak association for all-cause mortality (ERR = 0.08; 95% confidence interval 0.00006, 0.17; P = 0.05). For incidence of solid cancer and leukemia, no significantly elevated rain exposure risks were observed in either city. These results failed to show deleterious health effects from rain exposure. While these data represent the most extensive set of systematically collected data on rain exposure of the atomic bomb survivors, they are limited by substantial uncertainties regarding exposures and missing individual data, so cautious interpretation is advised.